Exploring the preparation practices of teachers who organise secondary school ski trips in England and Wales. Issue 2 (1st February 2019) - Stanley, Michelle; Duncan, Michael J.; Price, Mike; Leddington Wright, Sheila; Coad, Jane
Abstract: Secondary schools across England and Wales understand the importance of offering young people the opportunity to experience activity-based trips. One of these fundamental trips is the ski trip which enables young people to experience new challenges and adventure. However, within England and Wales, skiing is an atypical activity due to the lack of accessibility to the slopes. Consequently, it is vital to effectively prepare young people for skiing to promote enjoyment and reduce the likelihood of injury. The purpose of this study was to explore the current practices in the preparation of school ski trips within England and Wales. An electronic survey was administered to secondary schools across England and Wales with 270 completed responses of schools which organise ski trips. Analysis revealed that there were no significant differences ( p  > 0.05) across the regions with information being shared with parents prior to the ski trip. Young people are informed on similar information prior to and during the ski trip across the regions ( p  < 0.05). However, there was a significant difference between respondents screening (33%) and not screening students (67%) ( p  > 0.01) and under half (47%) of schools provide their pupils with exercise programmes prior to the school trip. Overall, these findings appear that ski trip organisers are consistent across England and Wales with their education of the young person and the management of the ski trip. Although, the knowledge gained by organisers to prepare young people is gathered from a variety of different sources. Therefore, it is essential for evidence-based information to be shared and disseminated to ski trip organisers to provide best practice and to facilitate other schools in providing ski trips for their pupils.